The demand for money in Greece: evidence through a shopping-time technology model and cointegration - Απέργης, Νικόλαος Ε.; Καρπέτης, Χ.; Κωτσιοπούλου, Α.; Μιτακίδου, Ε.; Τσιακίρη, Θ. (SPOUDAI Journal of Economics and Business, 1999)
The objective of this paper is to estimate a long-run version of money demand in Greece through cointegration tests and over the period 1978-1995. The feature that distinguishes this paper from the conventional ad-hoc money demand models is that the money demand function is derived through a shopping-time technology which seems the proper approach when the reason for holding money balances is the motive of minimizing the transactions costs.